Anomalias dentárias e polimorfismos genéticos como preditores do crescimento maxilo facial em indivíduos nascidos com fissuras labiopalatinas - Lacerda, Rosa Helena Wanderley (2022)
Introduction: Cleft lip and palate is the most common congenital anomaly in the human face. Most cases of cleft lip and palate have a multifactorial, polygenic etiology, which may be associated with environmental factors. The effect of surgical treatment on the facial bone growth pattern in patients with cleft lip and palate is well established in the literature. Several longitudinal studies have shown that the factor with the greatest impact on the results of surgical treatment is related to the surgeon's experience, however, the record of results that vary from excellent to unfavorable, even in surgeries performed by experienced surgeons, brings to light the need for investigating intrinsic variables that may be related to these treatment outcomes. In this study, the intrinsic factors studied included genetic polymorphisms and the frequency of dental anomalies. Objective: The aim of this study was to analyze genetic variation in MMP2, GLI2, TGFa, and FGFR2 and the frequency of dental anomalies as predictors of maxillofacial growth in patients born with cleft lip with or without cleft palate. Method: A cohort of 537 individuals born with cleft lip and palate, operated on by the same surgeon, was studied. Individuals between 7 and 14 years of age, with radiographic documentation, dental casts, and photographic documentation, before any orthodontic/orthopedic intervention, were included in the sample, and syndromic cases or those with incomplete clefts or microforms were excluded, totaling 360 individuals. As an outcome variable, maxillofacial growth was evaluated using lateral cephalometric radiography, using Wits and Nasion measurements perpendicular to point A and, in dental casts, using occlusal scores. As predictor variables, the polymorphisms MMP2 rs9923304, GLI2 rs3738880 and rs2279741, TGFA rs2166975, and FGFR2 rs11200014 and rs10736303, and the frequency of dental anomalies (clinical, photographic and radiographic evaluation) were evaluated. Analysis of initial cleft lip and palate size (in pre-surgical photographs and dental casts) as a predictor of growth outcomes was investigated as a secondary outcome. The variables age at which the primary surgeries were performed (cheiloplasty and palatoplasty) and the individual's age on the date of examination, sex and, laterality of the cleft were considered confounding variables. Statistical analysis: Statistical analysis was performed considering a confidence interval of 95%. The results of maxillofacial growth, with a minimum of 4 years, were evaluated using the Wilcoxon test. The predictive variables were analyzed in association or correlation with outcome variables using chi-square test, multivariate analysis, logistic and linear regression. The possible interaction between the SNPs was tested using chi-square. Results: An association was found between the frequency of dental anomalies and the results of maxillofacial growth in the total sample (p<0.0001). Maxillofacial growth was associated with dental anomalies in individuals born with unilateral cleft lip and palate (p<0.0001), and in cases born with bilateral cleft lip and palate (p<0.0001). Maxillofacial growth was associated in cases born with unilateral cleft lip with tooth agenesis (p=0.03). In cases born with unilateral cleft lip and palate, associations between maxillofacial growth and tooth agenesis (p=0.03), enamel structural anomalies (p<0.0001), and shape anomalies (p<0.0001) were found. In cases born with bilateral clefts, maxillofacial growth was associated with enamel structural anomalies (p=0.02), eruptive anomalies (p=0.04), and shape anomalies (p=0.01). We found an association between MMP2 rs9923304 and maxillofacial growth (p<0.0001). Individuals with the rare T variant had 4.5 times increased chance for maxillary retrognathism and the need for orthognathic surgery. There was also an association between GLI2 rs3738880 and maxillary growth outcomes in individuals born with unilateral cleft lip and palate (p=0.02), with an increased risk of 1.43 times for worse growth prognoses when the rare allele G is present. Statistical evidence for interaction between MMP2 rs9923304 and GLI2 rs3738880 was observed in individuals with two copies of rare alleles in both SNPs compared to individuals with no copies of rare alleles, with the chance of maxillary retroposition increased by 78 times (p<0.0001). TGFa rs2166975 was associated with maxillary retroposition in individuals born with unilateral cleft lip and palate (p=0.004) and FGFR2 rs11200014 was associated with maxillary retroposition within the total sample (p=0.005), with no preference with any specific type of clefts. The severity of the defect and the age at the date of the surgery variables did not present association with the variables related to maxillofacial growth. Conclusions: MMP2 rs9923304, GLI2 rs3738880, TGFa rs2166975, and FGFR2 rs2166975, as well as the presence of dental anomalies, can be used as variables that predict a trend of maxillofacial growth.